STRATEGI GREENWASHING: APAKAH PERUSAHAAN BENAR – BENAR PEDULI TERHADADAP LINGKUNGAN ATAU SEKEDAR GIMMICK? - Adjam, M Alif Satria; Hakim, Muhammad Zaidi (Sekolah Tinggi Manajemen IPMI, 2025)
Amid growing consumer awareness of environmental issues, companies worldwide are increasingly adopting marketing strategies that emphasize sustainability and social responsibility. However, the practice of greenwashing, where companies merely pretend to care about the environment to enhance their image, has raised significant concerns. This research aims to identify how greenwashing is used within the context of strategic management and to evaluate its impact on consumer trust and corporate reputation in the long term. The study employs a case study method, analyzing companies accused of greenwashing, particularly from the fast fashion and energy industries. The findings reveal that while greenwashing can boost short-term sales and popularity, its detrimental effect on corporate reputation becomes evident in the long run, especially when consumers detect the discrepancy between a company's claims and actual practices. The implications of this research highlight the importance of authentic sustainability strategies and contribute to the literature on ethics in strategic management. Thus, this study encourages companies to adopt more socially and environmentally responsible solutions, rather than mere image-building efforts.